2002
DOI: 10.1021/ja017281a
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Melting of Silica-Encapsulated Gold Nanoparticles

Abstract: We report on the size dependence of the melting temperature of silica-encapsulated gold nanoparticles. The melting point was determined using differential thermal analysis (DTA) coupled to thermal gravimetric analysis (TGA) techniques. The small gold particles, with sizes ranging from 1.5 to 20 nm, were synthesized using radiolytic and chemical reduction procedures and then coated with porous silica shells to isolate the particles from one another. The resulting silica-encapsulated gold particles show clear me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
393
2
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 520 publications
(423 citation statements)
references
References 29 publications
26
393
2
2
Order By: Relevance
“…A decrease in melting point was attributed to the diffusion of metal atoms at the surface of the metal NPs, which increases with the rise in temperature. Later on, a dependence of the melting temperature on a size of a gold NP was studied by Cleveland et al 11 and Dick et al 12 Recently, a coalescence of either silver or gold NPs was shown to take place even at room temperature 13,14 . The process, which is triggered by the removal or delocalization of the capping molecules at the surface of the NPs, takes place spontaneously once two NPs come into contact due to atom diffusion at the surface.…”
mentioning
confidence: 99%
“…A decrease in melting point was attributed to the diffusion of metal atoms at the surface of the metal NPs, which increases with the rise in temperature. Later on, a dependence of the melting temperature on a size of a gold NP was studied by Cleveland et al 11 and Dick et al 12 Recently, a coalescence of either silver or gold NPs was shown to take place even at room temperature 13,14 . The process, which is triggered by the removal or delocalization of the capping molecules at the surface of the NPs, takes place spontaneously once two NPs come into contact due to atom diffusion at the surface.…”
mentioning
confidence: 99%
“…The temperature is estimated as 573 K at the energy of 0.12 J according to a thermal diffusion model. 30 Figure 1(d) shows the melting of nanoparticles at a pulse energy of 0.2 J, which corresponds to a temperature of 450 C. The melting of Ag NPs is identified at this stage, which results in the remarkable shape change and coarsening of Ag NPs. Differences between thermal sintering and pulsed laser annealing are also obvious.…”
Section: Resultsmentioning
confidence: 96%
“…Thus, it is significantly lowered in small particles, e.g., 1.5 nm gold particles encapsulated in silica have been observed to melt at 380 °C compared to 1086 °C for bulk gold [11]. Additionally, other related properties such as sintering and annealing show similar size dependence.…”
Section: Introductionmentioning
confidence: 99%